PEMANFAATAN WISATA MATA AIR YANG DIKELOLA OLEH BUMDES DI DESA BELIK - Wafia Silvi Dhesinta Rini; Muhammad Insan Tarigan (Universitas Muhammadiyah Malang, 2020)
Belik Village has the potential to be developed into a tourist area or tourist village. The potential possessed by Belik Village is a spring located in a bamboo forest. Furthermore, the location of the bamboo forest is on a 4 hectare village treasury land so that the management and utilization of the spring can be used as a source of village cash receipts. The source of the springs will sound the gurgling among the bamboo forests located in Jibru Village, Belik Village so that it becomes a selling point for the development of ecotourism. The method used is descriptive qualitative and data obtained through interviews and field observations. Constraints experienced by village officials to the extent that they have not been able to establish a tourist village are caused by several things including (1) the non-establishment of a Village Regulation governing the establishment of a Bumdes; (2) there is no roadmap for tourism villages yet; (3) inadequate human resource capacity; and (4) limited innovations that support the tourism sector. Seeing the existing potential and some problems in Belik Village, Trawas District, intensive and inclusive assistance is needed to support the realization of the development of a tourism village based on the superior potential of the village. Keywords: tourist village, Bumdes, Village Regulation, Belik Village, Trawas District